Opioid prescribing rates from the emergency department: Down but not out. (1st December 2019) - Ali, Mir M.; Cutler, Eli; Mutter, Ryan; Henke, Rachel Mosher; Mazer-Amirshahi, Maryann; Pines, Jesse M.; Cummings, Nicholas
Highlights: 15–20% of ED visits resulted in opioid prescriptions filled. Opioid ED prescription rates increased from 2005–2010 and then declined through 2016. Average number of opioids dispensed from ED (18–20) remained steady. Whites were more likely to be prescribed opioids in the ED compared to Blacks. Abstract: Introduction: To examine opioid prescribing rates following emergency department (ED) discharge stratified by patient's clinical and demographic characteristics over an 11-year period. Material and methods: We used 3.9 million ED visits from commercially insured enrollees and 15.2 million ED visits from Medicaid enrollees aged 12 to 64 over 2005–2016 from the IBM® MarketScan® Research Databases. We calculated rates of opioid prescribing at discharge from the ED and the average number of pills per opioid prescription filled. Results: Approximately 15–20% of ED visits resulted in opioid prescriptions filled. Rates increased from 2005 into late 2009 and 2010 and then declined steadily through 2016. Prescribing rates were similar for commercially insured and Medicaid enrollees. Being aged 25–54 years was associated with the highest rates of opioid prescriptions being filled. Hydrocodone was the most commonly prescribed opioid, but rates for hydrocodone prescription filling also fell the most. Rates for oxycodone were stable, and rates for tramadol increased. The average number of pills dispensed from prescriptions filled remained steady over the study period at 18–20. Discussion: Opioid prescribing rates from the ED have declined steadily since 2010 in reversal of earlier trends; however, about 15% of ED patients still received opioid prescriptions in 2016 amidst a national opioid crisis. Conclusions: Efforts to reduce opioid prescribing could consider focusing on the pain types, age groups, and regions with high prescription rates identified in this study.